Some neural and hemato-immune factors correlated with lysozime saliva level in children living on territories polluted by radionucleides - T S Seniv; R A Seniv; I S Flyunt; M R Uhryn; W Zukow (Journal of Education, Health and Sport, 2015)
Seniv T S, Seniv R A, Flyunt I S, Uhryn M R, Zukow W. Some neural and hemato-immune factors correlated with lysozime saliva level in children living on territories polluted by radionucleides. Journal of Education, Health and Sport. 2015;5(5):275-282. ISSN 2391-8306. DOI 10.5281/zenodo.17737